Pseudoaneurysm of the mitral-aortic intervalvular fibrosa: A discovery of a late complication - Barrantes, Ciro (2020)
This is the case of a 46-year-old man, asymptomatic, with a history of single-disk mechanical aortic prosthesis implanted 25 years ago, who was incidentally diagnosed with a pseudoaneurysm of the mitral-aortic intervalvular fibrosa (a region of fibrous tissue located between the anterior leaflet of the mitral valve and the left and non-coronary aortic leaflets) discovered by means of a transthoracic echocardiography, transesophageal echocardiography and cardiac computed tomography. Surgery was decided because of the size of the pseudoaneurysm. This article shows the late presentation of a pseudoaneurysm in this location caused by a complication of an aortic valve replacement due to endocarditis. It also highlights the asymptomatic evolution, the size of the pseudoaneurysm and the election of a valve preserving surgery because the valve was not compromised. The different imaging techniques are complementary to the research and help to make the pertinent decisions.